2022
DOI: 10.1097/md.0000000000032082
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of cardiovascular and cerebrovascular diseases in young and middle-aged adults: A meta-analysis

Abstract: Background: The risk factors for cardiovascular and cerebrovascular diseases in young and middle-aged people have not yet been determined. We conducted a meta-analysis to find the risk factors for cardiovascular and cerebrovascular diseases, in order to provide guidance for the prevention of diseases in the young and middle-aged population. Methods: We searched PubMed, Embase, Cochrane Library from the establishment of the database to Mar 2022. We included case-control or cohort studies reporting risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Subgroup analysis indicated a strong inverse correlation between egg consumption and incident CED among participants who have been married and not currently smoking. Smoking is a significant risk factor for CED [33]. Findings from the Australian prospective study of cardiovascular risk showed that of 36 subtypes of CVD, 29 event rates were significantly increased in current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis indicated a strong inverse correlation between egg consumption and incident CED among participants who have been married and not currently smoking. Smoking is a significant risk factor for CED [33]. Findings from the Australian prospective study of cardiovascular risk showed that of 36 subtypes of CVD, 29 event rates were significantly increased in current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve meta-analyses described blood pressure as a risk factor. For stroke incidence, effect sizes ranged from 1.22 (95%CI:0.95-1.57) -1.66 (95%CI:1.51-1.81) for low pre-hypertension (120-129/80-84mmHg), 1.79 (95%CI:1.49-2.16) -1.95 (95%CI:1.73-2.21) for high pre-hypertension (130-139/85-80 mmHg) and 2.23 (95%CI:2.01-2.48) -10.92 (95%CI:7.07-16.86) for hypertension (>140/90 mmHg) (reference blood pressure < 120/80 mmHg) 36,[43][44][45][46][47][48] . For dementia incidence, effect sizes for hypertension ranged from 0.98 (95%CI:0.72-1.33) -1.41 (95%CI:1.23-1.62) [49][50][51][52] .…”
Section: Blood Pressurementioning
confidence: 99%
“…The major risk factors contributing to the CVD epidemic in Asia are the result of an intricate interplay between socioeconomic and living conditions, demographics, lifestyles, the prevalence of CVD risk factors, and the capacity to achieve prevention and treatment goals. In China, the risk factors for CVD and CBD in young people include obesity, current smoking, atrial fibrillation, hypertension, systolic blood pressure, and total cholesterol, while triglycerides serve as protective factors for CVD and CBD in young and middle-aged individuals [13]. A cross-sectional study showed significant variations in the prevalence of hypertension (24.5% in China, 17.6% in Korea, and 15.2% in Japan) and DM (8.9% in China, 5.7% in Korea, and 4.8% in Japan).…”
Section: Risk Factors Of Cvd and Cbdmentioning
confidence: 99%